2017
DOI: 10.1002/cbin.10889
|View full text |Cite
|
Sign up to set email alerts
|

CacyBP/SIP inhibits the migration and invasion behaviors of glioblastoma cells through activating Siah1 mediated ubiquitination and degradation of cytoplasmic p27

Abstract: Calcyclin-binding protein or Siah-1-interacting protein (CacyBP/SIP) has been reported to be up-regulated and plays an important role in promoting cell proliferation in human glioma. However, the effect of CacyBP/SIP on glioma cell motility is still unclear. Here, to our surprise, CacyBP/SIP was found to inhibit the migration and invasion of glioma cells U251 and U87. Silencing of CacyBP/SIP significantly promoted the migration and invasion behaviors of glioma cells. On the contrary, overexpression of CacyBP/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
(64 reference statements)
4
22
0
Order By: Relevance
“…Phosphorylation modifications predominantly mediate the regulation of P27 Kip1 's cellular localization, among which Ser10 phosphorylation promotes P27 Kip1 nuclear export via CRM1 protein 34, 43, and Thr157 or Thr198 phosphorylation, in a less common way, impairs P27 Kip1 nuclear import under serum stimulation 44. As P27 Kip1 is a known downstream target of both CACYBP and RNF41, a previous study has described that CACYBP aids in the degradation of cytoplasmic P27 Kip1 by Siah1 45, and RNF41 reduces the level of cytoplasmic P27 Kip1 via suppression of ERBB3-Akt signaling 46, thus causing effects on the migration and invasion abilities of glioma cells. Apart from increasing cellular migratory activity, cytoplasmic P27 Kip1 has also been reported to suppress apoptosis in breast cancer 47 and enhance proliferation in trophoblast cells 48.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation modifications predominantly mediate the regulation of P27 Kip1 's cellular localization, among which Ser10 phosphorylation promotes P27 Kip1 nuclear export via CRM1 protein 34, 43, and Thr157 or Thr198 phosphorylation, in a less common way, impairs P27 Kip1 nuclear import under serum stimulation 44. As P27 Kip1 is a known downstream target of both CACYBP and RNF41, a previous study has described that CACYBP aids in the degradation of cytoplasmic P27 Kip1 by Siah1 45, and RNF41 reduces the level of cytoplasmic P27 Kip1 via suppression of ERBB3-Akt signaling 46, thus causing effects on the migration and invasion abilities of glioma cells. Apart from increasing cellular migratory activity, cytoplasmic P27 Kip1 has also been reported to suppress apoptosis in breast cancer 47 and enhance proliferation in trophoblast cells 48.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CacyBP/SIP associates with Siah-1, Skp1, and TBL1 to form a ubiquitin ligase complex called SCF T BL1 -catenin by ubiquitination [10]. Recently, it was proposed that CacyBP/SIP could promote the interaction between Siah1 and cytoplasmic p27, which in turn increases the ubiquitination and degradation of cytoplasmic p27 [20]. In this study we showed that CacyBP/SIP interacted with Mdm2 to promote the ubiquitination of mutant Transcription factor p53 is reported to be activated by diverse genotoxic and cytotoxic stresses [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitinated substrates identified to date include p27 and β-catenin (5,19). Ubiquitinated substrates identified to date include p27 and β-catenin (5,19).…”
Section: Discussionmentioning
confidence: 99%